(untitled) (Research, Society and Development, 2021)
Objective: To analyze the records of biological samples collected for histopathological examination in the necroscopic reports of the Service of Ribeirão Preto (SVOI-RP) and to correlate records of histopathological results with records of causes of Death Verification mortality and morbidity. Methodology: Cross-sectional observational analytical study on data collected in necropsy reports, completed by pathologists and filed at the SVOI-SP, between 2014 and 2016. Results: 702 necroscopic reports were studied, with 1652 records of causes of mortality, 625 causes of morbidity and of 291 samples collected for histopathology. Discussion: Twenty-eight records of samples collected for histopathology with autolysis were used, with no significant correlation with quantity and quality of causes of morbidity and mortality. There was a greater record of cause of mortality in those reports without records of collected samples. Reports with records of more than seven samples had a lower amount of morbidities. Conclusion: There was no need for histopathological analysis to define diagnoses of mortality and morbidity. Standardizing the collection of samples could reduce costs, even without the impact of autolysis on the quantity and quality of causes of mortality and morbidity in the SVOI in Ribeirão Preto, São Paulo.